Чемпион среди неудачников: [роман ; 16+] / Марина Серова - Серова Марина Сергеевна (Русский бестселлер, 2015)
Экземпляры: Аб (20151221) / Инвентарный номер: 44307 / Цена: / Авт.знак: С 32 / ГРНТИ: 17.82.31 / ББК: 84(2Pос=Рус)6